Harmonic Morphisms Projecting Harmonic Functions to Harmonic Functions - M. T. Mustafa (Abstract and Applied Analysis)
For Riemannian manifolds M and N, admitting a submersion ϕ with compact fibres, we introduce the projection of a function via its decomposition into horizontal and vertical components. By comparing the Laplacians on M and N, we determine conditions under which a harmonic function on U=ϕ−1(V)⊂M projects down, via its horizontal component, to a harmonic function on V⊂N.